211k views
3 votes
Solve the system of equations using the linear combination method {5p-3q=-39 -2p-3q=3

P=
Q=

User Blackd
by
4.6k points

2 Answers

5 votes

Answer:

p=-6

q=3

Explanation:

User Amer Qarabsa
by
4.9k points
4 votes

Answer:

p=-6

q=3

Explanation:

5p-3q=-39

-2p-3q=3

Multiply the second equation by -1

2p +3q = -3

Add the first equation and the modified second equation

5p-3q=-39

2p +3q = -3

---------------------

7p = -42

Divide by 7

7p/7 = -42/7

p = -6

Now we can find q

2p +3q = -3

2(-6) +3q = -3

-12 +3q = -3

Add 12 to each side

-12+12 +3q = -3+12

3q = 9

Divide by 3

3q/3 = 9/3

q=3

User TheLetterN
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.